Evolving Conceptions of Ijtihad in Modern South Asia - Zaman, Muhammad Qasim (Islamic Studies, 2010)
This paper has three overlapping concerns. First, it reviews some instances of how the idea of ijtihad has figured in the discourses of the modern ‘ulama’. Second, it shows how the debates on this contested subject can shed some light on intellectual exchanges between Arab Middle Eastern and South Asian scholars and, more specifically, between the reformist Salafis of the Arab world and the Deobandi’s of the Indian subcontinent. It argues, finally, that the language and rhetoric of ijtihad have tended to increasingly recommend themselves to the ‘ulama’ as a way of rearticulating their claims to religious authority in the modern world.